Metal/mold thermal conductance affecting ultrafine scale microstructures in aluminum eutectic alloys - Kakitani, Rafael; Oliveira, Ricardo; Reyes, Rodrigo V.; Rodrigues, Adilson V.; Bertelli, Felipe; Garcia, Amauri; Spinelli, José E.; Cheung, Noé (Case studies in thermal engineering, 2021)
Ultra-thin microstructures of eutectic aluminum alloys have attracted attention due to their excellent mechanical properties. In this context, it is known that the massive production of industrial components may require adaptations in the processing routes with severe thermal control. Considering the benefits of molding applications, knowledge of proper conditions of the metal/mold interface is essential. The interfacial heat transfer efficiency controls the solidification kinetics and so the microstructure evolution. Furthermore, much of the existing work in this field involves the use of either water-cooled or massive copper molds. The goal is achieving moderate or fast cooling conditions and produce refined structures. In this sense, the association of the interfacial heat transfer coefficient, h, with desired microstructures can expand the application to other types of mold and process conditions. In this respect, the present research work applies a numerical mathematical model based on an inverse heat conduction problem (IHCP) for the solidification of relevant binary eutectic alloys, considered as priority for the production of ultrafine eutectics. It was demonstrated the compromise existing between the overall interfacial coefficient hg and the eutectic spacing for the Al-6.3 wt% Ni, Al-33 wt% Cu, Al-wt.12% Si and Al-1.0 wt% Co eutectic alloys. Expressions relating hg as a function of time (t) and hg versus the representative eutectic microstructural spacing (λ) of each alloy are proposed. The hg vs λ expressions allow inferring hg values necessary to induce the formation of ultrafine λ values.